State fish and wildlife agency culture: Access points to leverage major change. Issue 2 (1st February 2022) - Jacobson, Cynthia A.; Sullivan, Leeann; Gasta, Mark; Manfredo, Michael J.; Camuso, Judy; Novotny, Peter; Jacobson, Rick; Witthaus, Kendra
Abstract: Amid a time of unprecedented social‐ecological change, professionals within and outside of the US wildlife conservation community have called for transformation of existing processes and structures to ensure that the benefits of wildlife conservation can be realized well into the future. Current momentum behind an initiative to help increase conservation relevancy among population segments that have historically been underserved by the conservation community is underway. Sustainable institutional change will not be realized, however, without attending to internal cultural change within the conservation community itself. Although elements of an ideal institution have been suggested, specific interventions related to institutional culture need deeper exploration. State fish and wildlife agencies—a primary organizational actor within the conservation community—play a central role in institutional transformation. Using a systems framework, this essay describes key leverage points for cultural change for which interventions could result in sustainable culture shifts. Five possible interventions are introduced to stimulate conversation among conservation practitioners seeking to initiate transformational change within their specific cultural contexts. Abstract : Amid a time of unprecedented social change, professionals within and outside of the US wildlife conservation community have called for transformation to ensure its ability to provide benefits to society. State fish and wildlife agencies—a primary organizational actor within the conservation community—are a major focal point for needed change. Using a systems framework, this essay describes key leverage points for cultural change for which interventions could result in sustainable culture shifts. Five possible interventions are introduced to stimulate conversation among conservation practitioners seeking to initiate transformational change within their specific cultural contexts.